Infografis Pemetaan Perkiraan Bahaya Banjir di Kabupaten Waropen Berbasis Sistem Informasi Geografis Menggunakan arcGIS - Indora Restu Windesi; Gunawan Prayitno (Jurnal Teknologi dan Informatika, 2025)
Waropen Regency, located in Papua Province, Indonesia, is an area with abundant natural resource potential, such as fisheries (fish, shrimp, crabs), tropical forests and biodiversity. However, the varied topography, high rainfall and geographical conditions make this region vulnerable to flood disasters. This research aims to analyze and predict flood hazards in Waropen Regency using Geographic Information Systems (GIS) such as ArcGIS. The methods used include secondary data collection (topography, rainfall, land use, and river network), data processing using GIS software, as well as spatial analysis using Digital Elevation Models (DEM) and hydrological modeling. The research results produced a flood hazard zoning map that identifies priority areas based on threat level. This map is also used to analyze the potential impact of flooding on settlements, infrastructure and agricultural land. The findings of this research provide important information for local governments and stakeholders in designing disaster risk mitigation strategies, such as building flood control infrastructure and disaster mitigation-based spatial planning. Thus, this research shows the potential of GIS in supporting effective and data-based disaster risk management in Waropen Regency.